2020
DOI: 10.9734/aprj/2019/v3i230065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Density and Planting Pattern on Growth and Seed Yield of Groundnuts [Arachis hypogaea (l.)] in the Wet Middleveld of Eswatini

Abstract: The most appropriate plant density and planting pattern to use for optimum growth and yield of groundnuts (Arachis hypogaea L.) in Eswatini among those currently used is not known, as the patterns are highly influenced by environmental conditions in specific regions. A field trial was conducted with the objective of determining the optimum plant density and planting pattern for groundnut in the Wet Middleveld of Eswatini. The experiment was conducted at the University of Eswatini, Luyengo Campus during the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The data showed no significant difference in the interaction between plant density and row spacing for the 100-pods weight, 100-seeds weight. This outcome is consistent with the findings of Magagula et al (2019). In general, with increased plant density, the 100-pods weight and 100-seeds weight decreased; this might be due to the plants' wider spacing (Konlan et al, 2013).…”
Section: Yield Components and Yieldsupporting
confidence: 90%
See 2 more Smart Citations
“…The data showed no significant difference in the interaction between plant density and row spacing for the 100-pods weight, 100-seeds weight. This outcome is consistent with the findings of Magagula et al (2019). In general, with increased plant density, the 100-pods weight and 100-seeds weight decreased; this might be due to the plants' wider spacing (Konlan et al, 2013).…”
Section: Yield Components and Yieldsupporting
confidence: 90%
“…Our results are also consistent with previous studies; Rasekh et al (2010) found that LAI was also significantly influenced by the plant density during different growth stages. Magagula et al (2019) observed that the highest LAI value was 4.63-4.93, which declined to 1.93-2.47 as maturity. Effects of Plant Density and Row Spacing on Yield and Yield Components of Peanut (Arachis hypogaea L.) on the Coastal Sandy...…”
Section: Leaf Area Index (Lai)mentioning
confidence: 93%
See 1 more Smart Citation
“…LAI increased and was maximum during the pod formation period and decreased during harvest. Magagula et al (2019) observed that the highest LAI value was 4.63-4.93, which declined to 1.93-2.47 as maturity. Our results are also consistent with previous studies (Zhang et al, 2012;Jain et al, 2018;Mondal et al, 2020).…”
Section: Leaf Area Index (Lai)mentioning
confidence: 93%
“…According to the observations taken during the systematic conduction of the experiment with good maintenance of the experimental plots, we have concluded that as the branching of groundnut increases, the yield also increases, respectively. However, the extent of increase in yield and branching varies for different treatments and those differences in the yield obtained were given below: The number of branches led to an increase in yield based on different types of treatments in different experiments were reported in findings of Shashidhar VR, et al [3], Gowthami V, et al [4], Nigam SN, et al [5], Ali FM, et al [6], Avinasha BL, et al [7], Nagar R, et al [8], Oppong SD, et al [9], Thilini SPLNK, et al [10], Gawas D, et al [11], Magagula N, et al [12], Sathiya K, et al [13], Mohanty P, et al [14], Ibrahim II, et al [15], Yilmaz M, et al [16], Iddrisu A, et al [17], Singh N, et al [18], El Naim AM, et al [19], Seijo G, et al [20], Maleki SJ, et al [21], Michael CY, et al [22], Sanders TH, et al [23,24], Veeramani P, et al [25].…”
Section: Resultsmentioning
confidence: 95%